Estimativa da valorização imobiliária no município de Fortaleza - Faria, Leonardo Batisti de (2016)
Due to high prices of real estate in the city of Fortaleza, a survey was made of a history of behavior of these values over the last 3 years to work for a model in which shows the trend of increase in the value of the square meter in the neighborhoods of this capital. For this split the quarters in 4 groups and if it worked based on a WEAPON and ARIMA model in order to get up a forecast for the following months.